Assembly and analysis of the complete mitochondrial genome of Prunus davidiana (Rosaceae) - Zhang, Yuyan; Guo, Xin; Ma, Ruijuan; Yu, Mingliang; Xu, Jianlan; Shen, Zhijun (Frontiers in Plant Science, 2025)
Prunus davidiana is an excellent woody species with high resistance to various abiotic and biotic stresses. The species is also a potential gene donor due to its important developmental prospects. However, the characterisation of the mitochondrial genome (mitogenome) remains unexplored. In this study, we sequenced and assembled the mitogenome of P. davidiana using reads from Illumina sequencing and the Oxford Nanopore platform. According to the results, the P. davidiana mitogenome is 407,608 bp in length, with a GC content of 45.5%. It contains 64 genes, including 39 protein-coding genes, 22 tRNA genes and 3 rRNA genes. Codon usage, repetitive sequences, nonsynonymous to synonymous substitution ratios, RNA editing, synteny, and phylogenetic relationships among Rosaceae species and gene migration events were investigated. In addition, two novel indel markers were developed to distinguish several Prunus species (i.e. P. pseudocerasus, P. armeniaca, P. salicina and P. davidiana). The results of our analyses provide valuable information and a theoretical basis for future research on P. davidiana.